Alternative formulations of sorafenib for use in children. Issue 10 (20th June 2013) - Navid, Fariba; Christensen, Robbin; Inaba, Hiroto; Li, Lie; Chen, Zhaoyuan; Cai, Xiangjun; Regel, Joshua; Baker, Sharyn D.
Abstract Background Sorafenib is an oral multikinase inhibitor with antiangiogenic and antitumor activity. In most cases, the commercially available 200 mg tablet is not suitable for administration to children. We studied the chemical and physical stability of extemporaneously prepared formulations and evaluated the pharmacokinetic profile of cut tablets and smaller‐dosage capsules of sorafenib in children. Procedure Commercially available 200 mg tablets of sorafenib tosylate were used to prepare liquid suspensions of sorafenib in oil and Ora‐Plus®:Ora‐Sweet® solution, and to prepare 5, 10, 20, 50, and 100 mg capsules. Plasma concentrations of sorafenib were measured in patients receiving capsules and cut tablets, using a validated HPLC‐based method with tandem mass spectrometric detection. Results At room temperature and under refrigeration, sorafenib concentrations in Ora Plus®:Ora Sweet® were highly variable (means ranging from 75% to 131% of the intended concentration of 50 mg/ml). In oil suspension, sorafenib concentrations were inconsistent during compounding. In contrast, all smaller‐dosage capsules, except the 5 mg capsule, were within 91–99% of the intended content and were stable at room temperature for at least 8 months. Sorafenib pharmacokinetic parameters in patients receiving capsules or cut tablets were consistent with those reported previously in adults and children receiving intact tablets. Conclusions Sorafenib is not stable in an oral suspension prepared from commercially available tablets, but compounded capsules in smaller‐dosage forms that can be sprinkled on food or cut tablets are alternatives for administration to children who need smaller doses based on body surface area or cannot swallow tablets. Pediatr Blood Cancer 2013;60:1642–1646. © 2013 Wiley Periodicals, Inc.